Le corps dans les contes fantastiques et cruels de Maupassant - Oztokat Kılıceri, Nedret (Istanbul University Press, 2021)
Guy de Maupassant is one of the most illustrious writers of nineteenth-century French literature; he derives his glory from his consummate art of storytelling and novel writing. Drawing his inspiration from the original style of Flaubert, his master, Maupassant's skills are reflected in the fruit of his desire for accuracy and observation in the treatment of subjects still unpublished. The reading of his tales informs the reader about Maupassant's respect for the "patient teachings" lavished by the master who never ceased to remind him that there resides in everything an aspect still unexplored. The tales of Maupassant are a part of the apogee of the art of storytelling seen in the nineteenth century. His stories deliver a clear and accurate vision of his society at the time. In his prolific work, fantastic and cruel tales depict the human heart in very dark colors. In all Maupassant's tales and short stories, the author reveals himself as an outstanding analyst of the human soul whose uncertain and unpredictable meanderings he likes to draw. The fantastic and cruel tales of Maupassant, the subject of this book, offer a perfect example of the writer's ingenuity and of the particularly gloomy universe he populates with characters doomed by implacable destinies. Maupassant's way of feeling and seeing the world at the end of the nineteenth century combines skillfully with the addition of the author's taste for the real and the concrete. This study on the fantastic and cruel tales of Maupassant is a continuation of an earlier reflection on the cruel tale, following my doctoral work on Les Diaboliques of Barbey d'Aurevilly in 1995. The pessimistic vision nourished by the decadence of the end of the nineteenth century dear to the Norman novelist was reflected in his singular narrative and enunciation. In this writing filled with fine and rare qualities, I discovered the role of extraordinary beings as narrative agents. The diabolical nature of the Aurevillian characters appeared from behind their masks of decency and dignity, yet another reason to marvel at the unforeseen discoveries of literary analysis. My reading of Barbey d'Aurevilly's Les Diaboliques focused on narration and enunciation. I was also able to demonstrate, at the narrative level, that the taste for the dark and the diabolical needed the presence of a person with flesh and bone: his sinister projects, his disturbing existence, and his perverse aspirations, everything led back to his corporal viii presence in literary discourse. This mechanism unearthed in Barbey d'Aurevilly is one of the inspirations for the present analysis. However, the primary reason is to be found in my analytical approach. The semiotics of discourse situated the subject and its place in the semantic process at the center of the scholarly reflection. The existence of the character thus became the new concern of literary semiotics. In the light of the model of discursive and subjective semiotics, this book proposes to approach the fantastic universe of Maupassant from the collection of tales gathered, annotated, and presented by Marie-Claire Banquart and published by Garnier-Bordas in 1989 under the title of Guy de Maupassant Le Horla et autres Contes cruels et fantastiques. The present analysis on Maupassant succeeds the first version written in 1999 in a manuscript whose publication was delayed for various reasons. The reader will find here the latest version of my analysis reworked and written during my sabbatical. It makes no other claim than to be a reflection among others on the writing of Maupassant, an inexhaustible source for literary research. My biggest wish is that it inspires the pleasure of research and proposes a new way of reading for this great author.